(untitled) (Bhartiya Knowledge Systems, 2024)
This paper highlights the basic traditional medicinal practices in the context of Manipur, especially among the Meitei society. It also explained the local notion of diseases and various traditional healing practices over the generations. It reveals the role of the medicinal practitioners, which is an integral part of the socio-cultural and economic institutions of the Meiteis people in Manipur State of India.